Unilateral renal agenesis: case review of ambulatory pediatric nephrology clinics in Cali (Colombia Medica, 2010)
Introduction: Unilateral renal agenesis is a frequent renal malformation with incidence of 1 per 1000 live born children. There are no statistics nor protocols to manage and follow-up these patients. Usually asymptomatic, it can be early detected by prenatal ultrasound, allowing opportune detection and adequate follow up. The goal is to describe main features found in children with renal agenesis at four ambulatory pediatric nephrology clinics in Cali, Colombia: Hospital Universitario del Valle (HUV), Club Noel Children’s hospital and the private practice of two pediatric nephrologists. Methods: This is a retrospective descriptive study in a series of cases with congenital renal agenesis diagnosed between January, 1995 and December 2007, of patients under 18 years of age and based on a review of clinical records. Results: 43 patients were found, 51.2% males, 88% from the department of Valle del Cauca. Prenatal diagnoses were conducted in only 21% of these patients; agenesis was right in 48.8% and left in 51.2%. In 46.5%, association with other pathologies was found: occult spinal bifida, congenital scoliosis, and Klippel-Feil sequence. Compensatory renal hypertrophy was reported in 39.5% of the patients, 42% had episodes of urinary tract infection, 31% vesicoureteral reflux and 10% proteinuria. Four male patients (9.3%) developed renal failure. The average follow-up was 6.6 years. Conclusions: Prenatal diagnose was not very frequent in our set of cases. Urinary tract infection and vesicoureteral reflux were common, increasing the risk of renal deterioration. Prolonged follow up is suggested, with unified protocols to prevent renal failure.